Estimating the willingness to pay by the people in Kaysone Phomvihane City Savannakhet Province towards the development of Buengwa Tourist Attraction through the: used of CVM Approach - VONGKEO, Somphone; TOUNMANYSONE, Thongsa; BANMANIVONG, Lidsada; LATSAVAT , Soulang; MONEPADITH, Soksay (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
Study on estimating the willingness of urban residents in Kaysone phomvihanh City, Savannakhet Province to pay for the Berng Wa (Wa lake) Attraction Development: by utilizing CVM approach, The objective of this study was to estimate the willingness to pay (WTP) and seeks to identify the factors affecting WTP of urban residents in Kaysone phomvihanh City, Savannakhet Province for the Berng Wa (Wa lake) Attraction Development. WTP was estimated using a Contingent Valuation Method (CVM) approach through an open-ended questionnaire. administered to participants an Ordinary Least Square was applied to analyze the data: OLS regression conducted by (Davidson, R. And Mackinnon, J.G. 2004) Data used for analysis obtain from sampling urban residents in Kaisonephouvihanh City with a 400 person sample size in 2019. The results showed that the willingness of the people to pay for the development of Buengwa tourist site has the highest average value of 30,263.5 Kip / month / household, which shows that the people in Kaysone Phomvihane are willing to pay twice (30,263.5 x 125,622 = 3,801,761,397 kip/ year). For factors that influence or determine willing to pay people in a city far taught to develop tourism Attraction, and the test statistic that factors: the household (Family Income) distance between the attractions (Distance), the status of the respondents (Statute) and the size of the house (House hold) with a confidence level of 99% and 95%, for this research is good information to entities related to how to manage projects or developing tourism in the future.